A Tale of Two Twitterspheres: Political Microblogging During and After the 2016 Primary and Presidential Debates. (December 2019) - Berman, Ron; Melumad, Shiri; Humphrey, Colman; Meyer, Robert
In this research, the authors study the process by which social media posts are created and shared during live political debates. Using data from over 9.5 million tweets posted during and shortly after four key debates leading up to the 2016 U.S. presidential election, the authors test a series of hypotheses about how tweeting evolves over time during such events. They find that (1) as the debates progressed, the content of the "Twittersphere" became increasingly decoupled from the live event, and (2) the drivers of the success of tweets during the debates differed from the drivers of success observed after the debates. During the debates, users acted akin to narrators, posting shorter tweets that commented on unfolding events, with linguistic emotionality playing a limited role in sharing. However, when the debates were over, users acted more like interpreters, with successful posts being more elaborate and visually and emotionally rich accounts of the event. Evidence for the generalizability of the findings is provided by an analysis of Barack Obama's last State of the Union Address, where similar dynamics are observed.